VERBS IN TRANSLATION AND INTERPRETATION, CHALLANGES IN TRANSLATING VERBS IN ENGLISH AND UZBEK LANGUAGEAS DUE TO CULTURAL AND LONGUISTIC NUANCES (Konferensiyalar | Conferences, 2024)
This research paper will address the complexities of translating verbs between Uzbek and English. The study will begin by exploring the specific linguistic features related to these verbs and it delves into the challenges that arise due to cultural nuances (subtle, often unwritten aspects of a culture). Translation difficulties will be analyzed, and strategies for addressing those difficulties will be proposed. The paper emphasizes the importance of understanding both linguistic and cultural differences for achieving the most effective translations.